Certification of Organic Agriculture for rice production in Indonesia - Dedik Budianta; Yuanita Windusari; Supriyadi Supriyadi; Sri Yuliartini (Faculty of Agriculture, Universitas Sebelas Maret, 2016)
To make better the life, it is required safety foods for health. The health foods can be satisfied by organic farming that have more expensive price compared to foods derived from conventional agriculture. Organic farming is farming system based on biomass recycling or eliminating the use of materials as a synthetic agrochemical inputs. To determine whether the result of rice called as a organic product needs to be certified by the Organic Certification Board (OCB). According to the Indonesian National Standard 6729: 2013, organic farming systems are not only limited to not use material agrochemical synthetic, but must meet the requirements of organic farming systems in rice cultivation ranging from handling, storage, processing, transportation, labeling, marketing, production facilities, additional materials and other materials that are allowed start on farm to off farm should be separated from conventional agriculture. The farm is just a negate the use of agrochemicals and synthetic based on recycling without regard to the cultivation process and the system of post-harvest organic results are said to be food premium is not as organic food, because organic food is food produced from organic farming systems by applying processing practices to preserve the ecosystem of sustainable, control of weeds, pests, diseases, selection and crop rotation, water management, land preparation and planting and the use of biological materials. Thus the system of organic agriculture is a holistic production management system to improve and develop the agro-ecosystem health, including biodiversity, biological cycles and soil biological activity (Regulation of Indonesian Agriculture Ministry No. 64/2013). The first step that must be done is the conversion of land for food crops from anorganic to organic farming for 2 years did not get the requisite amount of agrochemical ingredients applied to the soil and 3 years for annual plants, after applying the organic farming system follows the Indonesian National standardization for organic farming. If agriculture in paddy soil can control the conventional farms into organic farming systems, then the resulting rice is as an organic product